Prevalence and associated factors of underweight among children 6-59 months of age in Takusa district, Northwest Ethiopia - Getnet Nigatu; Solomon Assefa Woreta; Temesgen Yihunie Akalu; Melaku Kindie Yenit (BMC, 2018)
Abstract Background Most of the nearly 104 million underweight children in the world lived in South East Asia and sub-Saharan Africa in 2010. According to the 2014 Ethiopian Demographic and Health Survey (EDHS) report, 24 and 7% of children aged 6-59 months were underweight and severely underweight, respectively. Although appropriate child feeding and nutritional interventions reduce child illness and death, malnutrition remains a leading public health problem in Ethiopia. As literature on the issue is scarce in northwest Ethiopia, this study aimed at determining the prevalence of under-weight and associated factors in children 6-59 months of age in Takusa district, northwest Ethiopia. Methods A community based cross-sectional study was conducted from January to February, 2017, at Takusa district, northwest Ethiopia. A total of 645 subjects were selected using the multi-stage sampling technique. Anthro software version 2.02 was used to determine the nutritional status of the children. A multivariable logistic regression analysis was used to investigate factors associated with underweight. Adjusted Odds Ratios (AOR) with the corresponding 95% Confidence Interval (CI) were used to show the strength of associations, and variables with P-values of < 0.05 were considered statistically significant. Results In this study, the overall prevalence of underweight was 19.5% (95% CI: 16.4-22.8). According to the multivariate analysis, urban residence (AOR = 0.60; 95% CI: 0.38-0.95), no antenatal care (ANC) follow up (AOR = 1.59; 95% CI 1.01-2.52), and mothers age (over 35 years) (AOR = 0.62; 95% CI: 0.38-0.99) were significantly associated with lower odds of underweight. Conclusion In the study community, the prevalence of underweight was lower than the findings of different studies in Ethiopia. Advanced maternal age (> 35 years), no antenatal follow up during pregnancy, and rural residence were significantly associated with underweight. Therefore, interventions targeting community management of acute malnutrition might be appropriate to manage the problem of underweight; efforts should also be intensified to reduce under-weight by focusing on identified determinants.